Effect of Price and Location on Purchasing Decisions (Case Study of CV. Sumber Anugrah Kota Bandung) - Faishal Rahimi (Universitas Kuningan, 2020)
This research discusses the effect of price and location on purchasing decisions that occur at CV. Sumber Anugrah Bandung. The sample used is 100 respondents or buyers from the store. This research is a causal research with Validity, Reliability, Classical Assumption testing, and Hypothesis testing. From this test, the results of the study indicate that Price and Location have a moderately positive effect on Purchasing Decisions. Price and location together have a significant influence on purchasing decisions.